Psychophysiological Prodromal Signs of Schizophrenic Relapse: A Pilot Study - Dawson, Michael E. (2010)
Do physiological changes occur shortly prior to psychotic relapse in schizophrenia outpatients? We addressed this question in a group of schizophrenia outpatients by measuring changes in symptoms and changes in activation of the sympathetic nervous system, as indexed by changes in skin conductance level (SCL), on a biweekly basis for between one and two years. All six outpatients exhibited heightened SCL within two weeks prior to relapse or exacerbation, compared to SCL proceeding continued remission. These results shed light on the psychotic relapse process and are consistent with neural diathesis-stress models of schizophrenia.